Analisis Faktor-Faktor yang Mempengaruhi Kecurangan Laporan Keuangan dalam Perspektif Fraud Pentagon - Aisyah Adepurwanty Rahman (JAF (Journal of Accounting and Finance), 2019)
Fraudulent financial reporting is a deliberate action for misstatement from the disclosure of financial statement that intended to deceive financial statement user in making economic decisions. This can be a serious problem because it can harm many parties. This research aims to examine and obtain evidence of the influence of fraud pentagon on fraudulent financial reporting, descriptively, simultaneously and partially. This research population includes infrastructure, utility, and transportation sector companies listed on the Indonesia Stock Exchange, 2016-2017. The sample collected by purposive sampling, which obtains 45 company with two years of observation. Therefore, there are 90 of the total sample researched. The analysis technique utilized the logistic regression using SPSS 24 software. The result shows that pressure, opportunity, rationalization, competence, and arrogance factors simultaneously affect the fraudulent financial reporting. Only the pressure factor partially affect the fraudulent financial reporting. Moreover, opportunity, rationalization, competence, and arrogance factors do not influence the fraudulent financial reporting.